2017
DOI: 10.1590/1678-992x-2016-0300
|View full text |Cite
|
Sign up to set email alerts
|

Fish and fishery products trade in Brazil, 2005 to 2015: A review of available data and trends

Abstract: Along the last ten years fish and fishery product trade in Brazil has been on a downward trajectory turning a profit of US$ 98.6 million in 2005 into a loss of US$ 1.25 billion by 2014. On the other hand, the country is a leading producer of grains and has the third largest animal feed industry in the world, which has added 5.5 million hectares of freshwater reservoirs and 3.5 million km 2 of an exclusive marine economic zone in the same period, a sizable potential for development of the aquaculture industry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…This fish species leads the fish farming in Brazil and presents high acceptance among consumers probably due to the mild flavor and easily removable fishbones (Associação Brasileira da Piscicultura, 2019; Monteiro et al, 2013). Maciel et al (2016) also reported a high frequency of citation of salmon and tilapia among Brazilian consumers, indicating that the consumption of native species is low (Barone, Lorenz, Sonoda, & Cyrino, 2017). In addition, although consumers have cited natural fish habitats, such as sea and river , they often do not know the specific habitat of the fish they consume (Vanhonacker et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…This fish species leads the fish farming in Brazil and presents high acceptance among consumers probably due to the mild flavor and easily removable fishbones (Associação Brasileira da Piscicultura, 2019; Monteiro et al, 2013). Maciel et al (2016) also reported a high frequency of citation of salmon and tilapia among Brazilian consumers, indicating that the consumption of native species is low (Barone, Lorenz, Sonoda, & Cyrino, 2017). In addition, although consumers have cited natural fish habitats, such as sea and river , they often do not know the specific habitat of the fish they consume (Vanhonacker et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Many of the species sequenced in this study were not even analyzed by IUCN, despite fishing pressures to which they are subjected. This is the case for the highly traded Argentine hake ( Merluccius hubbsi ), which is also one of the most consumed fishes in Brazil [ 59 ]. Providing more molecular resources for those species is a way to foment their study and assessments of their conservation status, leading to proper management actions.…”
Section: Discussionmentioning
confidence: 99%
“…Brazilian territory support great diversity of fish species (Reis et al, 2003;Lewinsohn & Prado, 2005;Toussaint et al, 2016). In addition, in recent years, aquaculture has intensified in Brazil, which may have contributed to the number of studies focusing on the body condition of fishes (Barone et al, 2017;Pelicice et al, 2017).…”
Section: Discussionmentioning
confidence: 99%